2019
DOI: 10.1177/1178221819866210
|View full text |Cite
|
Sign up to set email alerts
|

Vaping Expectancies: A Qualitative Study among Young Adult Nonusers, Smokers, Vapers, and Dual Users

Abstract: Background: “Expectancies,” or beliefs about outcomes, robustly correlate with and predict several behaviors including electronic nicotine delivery system (“e-cigarette”) use. However, there is limited qualitative research available regarding relevant e-cigarette vaping expectancies. Objectives: The present study used a qualitative approach to derive and refine e-cigarette expectancy themes among young adults. Methods: We conducted 12 focus groups and two individual interviews with young adult nonusers, e-ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
(89 reference statements)
2
24
0
Order By: Relevance
“…We found a weak positive correlation between vape use and the belief that vaping reduces stress (0.389, p = 0.000). Our data support those of others [ 14 ] who also reported that e-cigarette users believe that vaping reduces stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found a weak positive correlation between vape use and the belief that vaping reduces stress (0.389, p = 0.000). Our data support those of others [ 14 ] who also reported that e-cigarette users believe that vaping reduces stress.…”
Section: Discussionsupporting
confidence: 92%
“…Rates of e-cigarette use among high school students in the United States have strikingly increased from 1.5% in 2011 to 20.8% in 2018 [ 13 ], and these data have been corroborated in more recent studies [ 4 ]. In a qualitative study of young adults (N = 49), researchers [ 14 ] conducted focus groups and four main themes emerged: positive reinforcement, social benefits, negative effect reduction, and negative consequences. They found that many young adults were unsure of the negative consequences of vaping [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaping expectancies are beliefs about outcomes associated with vaping. 29 These beliefs can include social benefits such as social facilitation or influence on others. 29 Our findings support examining vaping expectancies as they may aid in more informed targets for interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Data show that adolescents think e-cigarettes are safer than combustible cigarettes, with some adolescents believing that e-cigarettes contain just water vapor without nicotine or other chemicals [14•, 26-28]. Several qualitative studies have found that adolescents do not fully understand the severity and negative consequences of nicotine addiction, compared with other types of addictions [29,30]. Coupled with these perceptions, recent studies show other proximal levels of influence, whereby adolescents are using e-cigarettes as a means to manage stress, anxiety, and depression [31][32][33].…”
Section: Why Adolescents Use E-cigarettesmentioning
confidence: 99%